DEVELOPMENT OF INDEPENDENT THINKING SKILLS OF CHILDREN IN A PRESCHOOL EDUCATIONAL ORGANIZATION - Madaminova Khusnida Rashidovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article we will discuss the benefits of developing independent thinking skills in preschoolers in a preschool educational organization.